ADOPTION ET DIFFÉRENCIATION DES SYSTÈMES DE CONTRÔLE DE GESTION PAR LES ÉTABLISSEMENTS PUBLICS MAROCAINS: UN ESSAI DE MODÉLISATION - Khalifa Ahsina; Omar Taouab; Mohamed Achraf Nafzaoui (European Scientific Journal, ESJ, 2014)
In most developed topic of management control in the public sector is in vogue countries (Gibert, 2002). However, in Morocco, the Moroccan public sector companies have often considered management control as a luxury (El ghadi , 2006) and its implementation seems too premature to report multiple priorities faced by the various companies in this sector . However, under the influence of fiscal and social pressures, the leaders of these companies are realizing the need to have a system of management control enabling them to take the path performance. This article aims to present the results of a survey of 41 companies and public institutions in Morocco and answer the following questions aim to : - How management control is practiced in companies and public institutions in Morocco? - And what are the factors that explain its adoption and differentiation? The results that we actually resulted showed that the differentiation of management control systems is explained by contingency factors, namely: the size, turnover, sector of activity, the screw position -à-vis the market and the type of control exercised by the State.